PRESERVING THE PURITY OF REVELATION - Muhibudin, Muhibudin; Jiwanto, Fahmi Islam; Maarif, Samsul (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2025)
This article critically examines the intersection of hermeneutics and the authority of the Qur’an, specifically focusing on its implications for interpreting sacred texts. It explores whether the hermeneutic method, which emphasizes historical context, textual dynamics, and reader subjectivity, poses a challenge to the Qur’an’s divine authority or whether it contributes positively to the tafsir tradition. The study contrasts the perspectives of classical scholars, such as Al-Suyuti, who adhered to a revelation-based tafsir methodology, with the views of modern scholars like Nasr Hamid Abu Zayd, who introduced a more contextualized approach to Qur'anic interpretation. By delving into the dynamics of meaning within hermeneutics, this paper investigates the potential risks of distortion (tahrif) that arise when the text is reinterpreted beyond its traditional exegesis. Furthermore, the article examines the role of hermeneutics in shaping contemporary interpretations of the Qur'an in the Indonesian context, particularly regarding sensitive issues such as gender and legal rulings. This exploration sheds light on the ongoing debate between maintaining the purity of the Qur’an’s meaning and adapting its teachings to meet the demands of modernity. Through a balanced approach, the study aims to provide recommendations for integrating hermeneutics into the tafsir tradition while ensuring that the Qur'an’s divine essence is preserved. In doing so, it underscores the importance of preserving the sacred text’s authority while making its teachings relevant to contemporary Muslim societies.